2023
DOI: 10.3390/polym15030506
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of SWCNTs as a Method of Improvement of Electrical and Mechanical Properties of CFRPs Based on Thermoplastic Acrylic Resin

Abstract: The aim of this research was to improve the electrical and mechanical properties of carbon-fibre-reinforced polymers (CFRP) based on thermoplastic acrylic resin ELIUM®, by introducing single-walled carbon nanotubes (SWCNTs) into their structure. The laminates were fabricated using the infusion technique of infiltrating the carbon fabric with the mixture of acrylic resin and SWCNTs. The addition of SWCNTs improved the electrical conductivity through the thickness of the laminate by several times compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…At elevated initial strains, the internal structure of the adhesive undergoes more significant deformation. This leads to greater alignment or stretching of the polymer chains and adhesive network, resulting in increased resistance to further deformation 25 . During relaxation, the internal structures may not completely revert to their original state, particularly at higher strain levels, likely due to physical entanglements and possible irreversible changes within the polymer network.…”
Section: Viscoelastic Behavior Of Psasmentioning
confidence: 99%
See 1 more Smart Citation
“…At elevated initial strains, the internal structure of the adhesive undergoes more significant deformation. This leads to greater alignment or stretching of the polymer chains and adhesive network, resulting in increased resistance to further deformation 25 . During relaxation, the internal structures may not completely revert to their original state, particularly at higher strain levels, likely due to physical entanglements and possible irreversible changes within the polymer network.…”
Section: Viscoelastic Behavior Of Psasmentioning
confidence: 99%
“…This behavior aligns with the time-temperature superposition principle typical of viscoelastic materials, where higher temperatures effectively accelerate relaxation processes 6 . Additionally, the temperature affects the relaxation mechanisms: at lower temperatures, PSAs exhibit a predominantly elastic response due to restricted molecular mobility, while at higher temperatures, a more pronounced viscoelastic response emerges due to increased molecular rearrangement 25 .…”
Section: Viscoelastic Behavior Of Psasmentioning
confidence: 99%
“…The addition of nanofillers to polymer matrices has been found to improve thermal and electrical properties and even lead to higher mechanical strength and stiffness. For example, the electrical conductivity of carbon fibre-reinforced thermoplastic composites was investigated and it was shown that the addition of single-walled carbon nanotubes to the matrix led to an improvement in electrical conductivity [10]. Similarly, studies on the thermal properties of graphene oxide modified epoxy composites were conducted and they showed that the resulting composites exhibited improved thermal stability and improved interlaminar shear strength ILSS values [11].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, it has been proven that resin modified with CNTs can improve the electrical conductivity of epoxy-based or thermoplasticbased nanocomposites 28,29 . Moreover, in previous work, it has been proven that modification of Elium® resin with a low content of SWCNTs improves the electrical conductivity of CFRPs by 4.5-5.6 times 30 .…”
mentioning
confidence: 98%